2022
DOI: 10.3390/healthcare10020325
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Medications for Severe Hypertension in Pregnancy: A Systematic Review and Meta-Analysis

Abstract: Background: Hypertension in pregnancy causes significant maternal and fetal mortality and morbidity. A comprehensive assessment of the effectiveness of antihypertensive drugs for severe hypertension during pregnancy is needed to make informed decisions in clinical practice. This systematic review aimed to assess the efficacy and safety of antihypertensive drugs in severe hypertension during pregnancy. Methods: A systematic review using the electronic databases MEDLINE (PubMed) and Cochrane Library was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 46 publications
0
6
0
2
Order By: Relevance
“…The specific pharmaceutical to treat hypertension during pregnancy should be carefully selected. Efficacy of antihypertensive pharmaceuticals was assessed by the risk of persistent severe hypertension ( Awaludin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The specific pharmaceutical to treat hypertension during pregnancy should be carefully selected. Efficacy of antihypertensive pharmaceuticals was assessed by the risk of persistent severe hypertension ( Awaludin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Severe preeclampsia is one of the conditions whereby guidelines recommend a more aggressive BP reduction to less than 140 mmHg SBP within 1 h of diagnosis [1]. A recent meta-analysis interestingly found that rapid-acting oral nifedipine resulted in the most sustained BP reduction; however, all the traditional agents: labetalol, nicardipine, and urapidil, were equally effective at the time to BP control [47 ▪ ].…”
Section: Other Conditionsmentioning
confidence: 99%
“…Studi meta-analisis menunjukkan penggunaan oral nifedipin pada pasien preeklamsia memberikan keberhasilan terapi yang lebih tinggi dibanding antihipertensi lainnya [17]. Studi lainnya menunjukkan bahwa penggunaan kombinasi antihipertensi tidak memberikan luaran neonatal yang lebih baik dibanding penggunaan antihipertensi tunggal [18,19].…”
Section: Pendahuluanunclassified
“…Metildopa bekerja di sistem saraf pusat melalui mekanisme agonis reseptor alfa dimana obat ini merupakan obat antihipertensi paling aman untuk ibu hamil [13]. Berdasarkan studi meta-analisis diketahui penggunaan metildopa selama kehamilan relatif lebih efektif dalam mengontrol tekanan darah dan tingkat efek samping yang lebih rendah dibandingkan dengan nifedipin [17].…”
Section: Hasil Dan Pembahasanunclassified